Relevance of Qualitative Research Approach in Evaluating Mental Health Interventions among Victims of Violence - Sara G. Pacichana-Quinayaz; Gisel V. Osorio-Cuellar; Stephanie Gonzalez; Francisco Javier Bonilla-Escobar; Maria I. Gutierrez-Martinez (University Library System, University of Pittsburgh, 2015)
NA